Analysis Of Islamic Family Law Renewal In Türkiye - Siska Kinasih (Penerbit Hellow Pustaka, 2023)
Turkey was the first country to reform Muslim Family Law, and the idea emerged in 1915. Legislation of new laws to complement Islamic law on a large scale was carried out by the Ottoman rulers in the 10th/16th century AD. produce qanun . The Turkish Civil Law further elevates the status of women, especially the prohibition of polygamy, the freedom for wives to file divorce claims for certain reasons, as well as equality in inheritance. The reform of Islamic law in the format of family law legislation began in 1917 with the ratification of The Ottoman Law of Family Rights (Law on family rights) by the Turkish Government. The reform of family law in Turkey is a milestone in the history of family law reform in the Islamic world and has had a major influence on the development of family law in other countries.